2010
DOI: 10.1590/s1984-46702010000500003
|View full text |Cite
|
Sign up to set email alerts
|

Historical relationships among Neotropical endemic areas based on Sepedonea (Diptera: Sciomyzidae) phylogenetic and distribution data

Abstract: The present study used the previously defined relationships among the snail-killing species of Sepedonea as the starting point for a cladistic biogeography analysis of endemic areas in the Neotropical region. The goal of the study was to use two different data sets to test the possible monophyly of two important biomes in the region: the Amazon and the Atlantic Forest. The possible historical significance of the arid biomes was also investigated. The study used Brooks Parsimony Analysis (Primary BPA). The area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
2
11
1
Order By: Relevance
“…Gomes de Carvalho et al . () suggested that the uplift of the Brazilian Central Plateau in the late Pliocene–early Pleistocene may have caused the isolation and differentiation of this area and may have split a former Amazonian plus Atlantic+Parana forests biogeographical unit (Costa, ; Nihei & Carvalho, ; Sigrist & Carvalho, ; Pires & Marinoni, ). Silva () and Costa () assumed that the Cerrado gallery forests harbour many Atlantic and Amazon species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gomes de Carvalho et al . () suggested that the uplift of the Brazilian Central Plateau in the late Pliocene–early Pleistocene may have caused the isolation and differentiation of this area and may have split a former Amazonian plus Atlantic+Parana forests biogeographical unit (Costa, ; Nihei & Carvalho, ; Sigrist & Carvalho, ; Pires & Marinoni, ). Silva () and Costa () assumed that the Cerrado gallery forests harbour many Atlantic and Amazon species.…”
Section: Discussionmentioning
confidence: 99%
“…Biogeographical analyses integrating both forest and open biomes of South America are uncommon (e.g. Costa, ; Sigrist & Carvalho, ; Pires & Marinoni, ; Morrone, ), even though South American forests support high levels of biodiversity and suffer the most severe deforestation in the world (Laurence, ). We have undertaken a preliminary evolutionary biogeographical analysis of South America based on records of a group of broad‐nosed weevils, the tribe Naupactini (Coleoptera: Curculionidae), which includes more than 600 species and 65 Neotropical genera (O'Brien & Wibmer, ; Wibmer & O'Brien, ).…”
Section: Introductionmentioning
confidence: 99%
“…The open biomes have been also analysed recently (Ramos and Melo, ; Werneck, ), but their integration with analyses of the areas with forest biomes is rare (e.g. Sigrist and Carvalho, ; Pires and Marinoni, ; Costa, ).…”
mentioning
confidence: 99%
“…This represents an example of dynamic vicariance, where climatic changes act displacing gradually a biotic component (Zunino 2003). Vicariance between the Amazonian and Parana subregions has been already detected by recent analyses (Costa 2002;Morrone 2002;Nihei & Carvalho 2004, 2007Sigrist & Carvalho 2009;Pires & Marinoni 2010), although patterns appear to be more complex. Costa (2002) found that the Amazonian and Parana forests were not exclusive in terms of their mammal species, overlapping broadly with Chacoan taxa.…”
Section: Individual Tracks Were Obtained For Five Species Of Entimusmentioning
confidence: 69%
“…Costa (2002) found that the Amazonian and Parana forests were not exclusive in terms of their mammal species, overlapping broadly with Chacoan taxa. Nihei & Carvalho (2007) and Pires & Marinoni (2010) hypothesized that the Amazonian subregion might be a composite area.…”
Section: Individual Tracks Were Obtained For Five Species Of Entimusmentioning
confidence: 99%